Communicating with Extension Clients about Water - Alexa J. Lamm; Phillip S. Stokes; Caroline G. Roper (EDIS)
The conservation and preservation of natural resources is one of the most pressing issues facing the nation today (Gregory & Di Leo, 2003). Among these natural resource issues are the issues of water quality and quantity. Water is one of the most important resources in the United States, and is especially important in Florida. Not only is Florida a specialty crop state, but the Florida economy also depends highly on tourism and recreation, both of which thrive on water. Water impacts Florida’s tourism, agriculture, retail, and real estate development industries, all of which significantly contribute to Florida’s economy (Odera, Lamm, Dukes, Irani, & Carter, 2013).